Prevalence of antibodies against SARS-CoV-2 according to socioeconomic and ethnic status in a nationwide Brazilian survey - Bernardo L Horta; Mariângela F Silveira; Aluísio J D Barros; Fernando C Barros; Fernando P Hartwig; Mariane S Dias; Ana M B Menezes; Pedro C Hallal; Cesar G Victora (Pan American Health Organization, 2020)
Objectives. To investigate socioeconomic and ethnic group inequalities in prevalence of antibodies against SARS-CoV-2 in the 27 federative units of Brazil. Methods. In this cross-sectional study, three household surveys were carried out on May 14-21, June 4-7, and June 21-24, 2020 in 133 Brazilian urban areas. Multi-stage sampling was used to select 250 individuals in each city to undergo a rapid antibody test. Subjects answered a questionnaire on household assets, schooling and self-reported skin color/ethnicity using the standard Brazilian classification in five categories: white, black, brown, Asian or indigenous. Principal component analyses of assets was used to classify socioeconomic position into five wealth quintiles. Poisson regression was used for the analyses. Results. 25 025 subjects were tested in the first, 31 165 in the second, and 33 207 in the third wave of the survey, with prevalence of positive results equal to 1.4%, 2.4%, and 2.9% respectively. Individuals in the poorest quintile were 2.16 times (95% confidence interval 1.86; 2.51) more likely to test positive than those in the wealthiest quintile, and those with 12 or more years of schooling had lower prevalence than subjects with less education. Indigenous individuals had 4.71 (3.65; 6.08) times higher prevalence than whites, as did those with black or brown skin color. Adjustment for region of the country reduced the prevalence ratios according to wealth, education and ethnicity, but results remained statistically significant. Conclusions. The prevalence of antibodies against SARS-CoV-2 in Brazil shows steep class and ethnic gradients, with lowest risks among white, educated and wealthy individuals.